Integration of Renewable Energies in Mobile Employment Promotion Units for Rural Populations - A. Laabid; A. Saad; M. Mazouz (Civil Engineering Journal, 2022)
The article aims to analyze, evaluate, and improve solutions for the integration of hybrid energy sources (Solar Photovoltaic PV/Batteries/Diesel Generator (DG)) in mobile service units (MSU), designed to provide services to rural populations (drug delivery, vaccination, training, employment promotion, bank, laboratory, etc.). The first objective is to evaluate the performance of two already deployed photovoltaic systems installed on the roofs of trucks, with respective powers of 2.12 and 3.54 kWp. Solar production, consumption, and SOC (State of Charge) of batteries are collected and analyzed. We modelled the energy conversion chain and simulated its behavior on all days of the year. Simulated results are then compared to the on-site measurements. Several association scenarios (PV/batteries) are then studied to propose the optimal combination, taking into account the surface offered for the installation of the PV modules (roof of the truck), the weight, and the lifespan of the batteries. The developed and deployed solution proposes more advantageous association scenarios (PV/Storage), and reduces the time of recourse to the DG. From this perspective, we simulated the operation of the hybrid system for the three battery capacities: 40,000, 31,680, and 19,200 Wh (~1667, 1320, and 800 Ah). The results reveal that the uncaptured energy for a 3540 Wp field is five times greater than that of a 2120 Wp field. On the other hand, the number of battery charge/discharge cycles is divided by ten. Doi: 10.28991/CEJ-2022-08-07-07 Full Text: PDF